S6K1 acts through FOXO to regulate juvenile hormone biosynthesis in the red flour beetle, Tribolium castaneum. (July 2022) - Jiang, Heng; Zhang, Nan; Ge, Huichen; Wei, Jiaping; Xu, Xin; Meng, Xiangkun; Qian, Kun; Zheng, Yang; Wang, Jianjun
Graphical abstract: Highlights: TcS6K1 is involved in fecundity and fertility in Tribolium castaneum . Knockdown of TcS6K1 promoted TcFOXO nuclear translocation. TcFOXO negatively regulated the expression of TcFDH . Abstract: As the downstream effector of the target of rapamycin complex 1 (TORC1) signaling pathway, the ribosomal protein S6 kinase (S6K) is an important regulator of insect reproduction, however, the underlying mechanism remains obscure. In this study, a S6K gene, named TcS6K1, was isolated from the red flour beetle, Tribolium castaneum. Analysis of temporal and spatial expression patterns revealed that TcS6K1 is expressed at the highest level in the one-day-old first instar larvae and head of 7-day-old females, respectively. RNAi-mediated knockdown of TcS6K1 in either female or male adults decreased the number of eggs laid, with a concomitant reduction of mRNA levels of vitellogenin genes, TcVg1 and TcVg2, two male accessory gland secretory proteins, as well as the juvenile hormone (JH) biosynthesis-related gene, farnesol dehydrogenase ( TcFDH ). While the mRNA and protein levels of the transcription factor forkhead box O (TcFOXO) were not affected, suppression of TcS6K1 expression promoted TcFOXO nuclear translocation to exert its transcriptional action. Further RNAi and EMSA analysis revealed that TcFOXO negatively regulated the expression of TcFDH . These results indicate that S6K might regulate beetles' reproduction through FOXO/JH signaling pathway.